2017
DOI: 10.1039/c6tb01978a
|View full text |Cite
|
Sign up to set email alerts
|

Post-nano strategies for drug delivery: multistage porous silicon microvectors

Abstract: Nanodelivery systems usually improve the biodistribution of drugs, leading to reduced side effects and enhanced therapeutic efficacy. However, only a small portion of the injected nanoparticle dose accumulates in pathological tissue. Challenges in drug delivery arise due to a multitude of transport obstacles in the body, including the endothelium, the extracellular matrix, and the cell membrane. In general, nanoparticles are designed to overcome only a few biological barriers, making them inadequate for locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 81 publications
0
36
0
2
Order By: Relevance
“…Also, surface deposition of Au nanoparticles or QDs can be used for special optical imaging, and the loading or deposition is also vastly dependent on the surface modification of PSi. [4k,47a] Tasciotti et al[4k] loaded QDs and single‐walled carbon nanotubes (SWNTs) into the hemi‐spherical PSi microparticles with a diameter of 3.2 µm and an average pore size of 30 nm, and further applied this nanocomposites into cellular fluorescence imaging. The results showed that carboxyl QDs, which had a negative surface charge (zeta potential, −32.8 mV), and PEG–FITC–SWNTs (zeta potential, −9.21 mV) could be loaded more efficiently into APTES‐modified PSi (zeta potential, +6.52 mV) than into oxidized PSi (zeta potential, −10.1 mV).…”
Section: Surface Chemistry and Modification Of Psimentioning
confidence: 99%
“…Also, surface deposition of Au nanoparticles or QDs can be used for special optical imaging, and the loading or deposition is also vastly dependent on the surface modification of PSi. [4k,47a] Tasciotti et al[4k] loaded QDs and single‐walled carbon nanotubes (SWNTs) into the hemi‐spherical PSi microparticles with a diameter of 3.2 µm and an average pore size of 30 nm, and further applied this nanocomposites into cellular fluorescence imaging. The results showed that carboxyl QDs, which had a negative surface charge (zeta potential, −32.8 mV), and PEG–FITC–SWNTs (zeta potential, −9.21 mV) could be loaded more efficiently into APTES‐modified PSi (zeta potential, +6.52 mV) than into oxidized PSi (zeta potential, −10.1 mV).…”
Section: Surface Chemistry and Modification Of Psimentioning
confidence: 99%
“…Thes ynthesis of Si particles with the aforementioned requirements represents along-standing challenge.Since the first observation of visible photoluminescence in porous Si, [21] great efforts have been made to produce Si nanomaterials with controlled size,p hase and morphology.Avariety of synthesis techniques has been explored to produce Si nanostructures for anodes in lithium-ion batteries, [22] light-emitting quantum dots (QDs), [23] light harvesting devices, [24] and drug delivery systems. [25] Past Reviews on Si have focused on Si exhibiting luminescent properties, [25,26] or as possible anodes for lithium batteries. [22] To date,all the Reviews and textbooks addressing Si for use in metamaterials discuss the fundamental optics behind its visible-light scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Seit der ersten Beobachtung der sichtbaren Photolumineszenz an porösem Si wurden große Anstrengungen unternommen, um Si‐Nanomaterialien von festgelegter Größe, Phase und Morphologie zu erzeugen. Erforscht sind zahlreiche Synthesetechniken, die Si‐Nanostrukturen für Anoden in Lithiumionenbatterien, leuchtenden Quantenpunkten (“quantum dots”, QDs), Lichtsammelvorrichtungen und Wirkstofftransport‐Systemen herstellen …”
Section: Einführungunclassified
“…Frühere Übersichtsartikel zu Silicium konzentrierten sich auf dessen Lumineszenzeigenschaften oder auf den möglichen Einsatz als Anode in Lithiumbatterien . Sämtliche Übersichten und Fachbücher, die sich mit Si zur Anwendung in Metamaterialien beschäftigen, behandeln auch die optischen Grundlagen der Streuung von sichtbarem Licht …”
Section: Einführungunclassified